2016
DOI: 10.1016/j.dci.2016.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Oral vaccination of fish: Lessons from humans and veterinary species

Abstract: The limited number of oral vaccines currently approved for use in humans and veterinary species clearly illustrates that development of efficacious and safe oral vaccines has been a challenge not only for fish immunologists. The insufficient efficacy of oral vaccines is partly due to antigen breakdown in the harsh gastric environment, but also to the high tolerogenic gut environment and to inadequate vaccine design. In this review we discuss current approaches used to develop oral vaccines for mass vaccination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
108
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(108 citation statements)
references
References 160 publications
0
108
0
Order By: Relevance
“…For instance, current research efforts aim to further investigate the role of mucosal immunity in teleost fish and characterize the immunopotentiating interactions with the gut microbiome [92]. Further, this systemic understanding has many applications for oral vaccination design and the development of protective responses within the fish [93] [94]. The future development and improved efficiency of immune-enhancing feedstuffs and disease management strategies should promote more superior yields and increase the sustainability of intensive aquaculture.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, current research efforts aim to further investigate the role of mucosal immunity in teleost fish and characterize the immunopotentiating interactions with the gut microbiome [92]. Further, this systemic understanding has many applications for oral vaccination design and the development of protective responses within the fish [93] [94]. The future development and improved efficiency of immune-enhancing feedstuffs and disease management strategies should promote more superior yields and increase the sustainability of intensive aquaculture.…”
Section: Discussionmentioning
confidence: 99%
“…Degradation of antigens in the highly tolerogenic gut environment is a main reason for limited efficacy of oral vaccines in fish. 14,15 In conclusion, the results of the genome sequence analysis reported here for V. mimicus provides genetic basis for the development of subunit and live attenuated vaccine. Moreover, immersion challenge test indicated that strain SCCF01 has the ability of colonization and adhesion to the mucosal surfaces, which is promising for attenuated vaccine development.…”
Section: To the Editormentioning
confidence: 99%
“…Effective routes for vaccine administration in fish include oral, immersion, dip or bath, anal intubation and injection (Li, Ma, & Woo, ). However, bath or immersion vaccination is the most practical method for small‐sized fishes, including fingerlings (Embregts & Forlenza, ). Furthermore, formalin‐killed and live attenuated vaccines are mucosal vaccines, which are suitable for bath or immersion vaccination in aquaculture (Soto, Griffin, & Tobar, ).…”
Section: Introductionmentioning
confidence: 99%